Diagnostic Limitation of Chikungunya Fever and its Future Prospect: A Review Update - Yeasmin, Mahmuda; Yusuf, Md Abdullah; Rahman, Muhibbur (Bangladesh Journal of Infectious Diseases, 2019)
Chikungunya is a febrile illness which is usually self-limiting caused by Chikungunya virus (CHIKV). It is transmitted bythe bites of infected adult female mosquitoes mainly Aedesaegypti and Aedesalbopictus from human to human; these vectors also transmit other viral diseases including dengue, zika virus and yellow fever. These viral diseases presented in a similar manner in their early stage of infection specially dengue and chikungunya since neither of them possesses any specific feature to be distinguished clinically. Their outcome and treatment strategies are distinct so early and accurate diagnosis is mandatory for better management and taking appropriate measures to prevent or reduce severity of complications. An early confirmation of any infection demands diagnostic tools that are highly specific and cost effective. Currently no diagnostic tool is available for CHIKV detection which can fulfill these criteria. Moreover effective surveillance, outbreak control, vaccine design and drug development all this demand proper diagnosis. In this review we focus on limitation of available laboratory tests related to diagnosis of chikungunya virus and discuss priorities for further studies needed for disease diagnosis in early stage to control the outbreaks Bangladesh Journal of Infectious Diseases, December 2018;5(2):65-70